Identifikasi dan Prevalensi Ektoparasit dan Endoparasit Pada Ikan Cupang (Betta sp.) - Agus Putra; Nurul Husna; Hanisah (Program Studi Budidaya Perairan Universitas Maritim Raja Ali Haji, 2022)
This study aims to determineethe types of parasites in betta fish. This research was conducted in February to March 2022. The research site was at Farm Irwan Fisheries Banda Aceh, while for the identification of parasites carried out attthe Fish Quarantine Station for Quality Control and Safety of Fishery Products Aceh. The method used in this research is descriptive analytic method. Purposive sampling was applied with 3 criteria: thin fish, very slow fish movement, and skin irritation. The results showed that the type of parasites were Gyrodactylus sp. Dactylogyrus sp., Trichodina sp. and Lernae sp. which found on the skin and gills. The highest prevalence was seen in the skin at 17% while the lowest prevalence was in the gills, the prevalence value was 12%. The value o fthe degree of infection in the skin is 4.85 while the lowest intensity in the skin was 0.2.